2022
DOI: 10.1186/s13229-022-00495-5
|View full text |Cite|
|
Sign up to set email alerts
|

The relevance of the interpersonal theory of suicide for predicting past-year and lifetime suicidality in autistic adults

Abstract: Background While there are known risk factors for suicidality in autistic adults, these are often unconnected from theoretical frameworks that might explain why risk is elevated and guide clinical interventions. The present study investigated the relevance of constructs from the Interpersonal Theory of Suicide (ITS), including perceived burdensomeness, thwarted belongingness and acquired capability for suicide, and explored mechanisms through which certain risk factors (relationship status, age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 99 publications
1
15
0
2
Order By: Relevance
“…The autistic sample ( n = 314) was the same as that described in a previous study [ 54 ]. They were recruited via advertisement on social media, Autistica’s research network and the Cambridge Autism Research Database; we also contacted participants on our mailing lists from previous studies [ 22 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The autistic sample ( n = 314) was the same as that described in a previous study [ 54 ]. They were recruited via advertisement on social media, Autistica’s research network and the Cambridge Autism Research Database; we also contacted participants on our mailing lists from previous studies [ 22 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ethical permission for the study was granted by the Science and Technology Faculty panel of Bournemouth University. Data for the present analysis were collected between July 2020 and March 2021 as part of a larger online study which involved a number of additional standardised questionnaires (see [ 54 ]). We describe only the measures relevant to the present analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following publication of the original article [ 1 ], the authors reported missing information in the ‘Acknowledgements’ section. The corrected ‘Acknowledgements’ section reads:…”
Section: Correction To: Molecular Autism (2022) 13:14 Https...mentioning
confidence: 99%